Family circumstances and the law violations of juvenile delinquency - A quantitative research in Vietnam - Xuan, Chau Hoang; Minh, Tuan Hoang; Ngoc, Ha Do; Nguyen, Thang The (International Journal of Innovative Research and Scientific Studies, 2025)
In Vietnam, juvenile delinquency is significant and growing, primarily due to various socio-economic and family issues. This study explores family circumstances (FC) in relation to juvenile crime, indicating how parental neglect can lead to domestic violence, economic hardships, and a lack of proper guidance, which set the stage for law violations committed by minors. Through the narration of legal cases, official reports, and sociological surveys, the research identifies the top family-related factors that propel juvenile delinquency. The research results indicate that unstable family realities, characterized by broken homes, lack of parental supervision, and demonstrations of criminal behavior, considerably increase the chances of youth offending. It highlights that stronger family-based interventions, social support systems, and reforms in juvenile justice policies are necessary for reducing youth crime rates in Vietnam.